Correlation Between Online Gaming Duration and Dry Eyes Complaints and Quality of Life Using DEQS Questionnaire - I Putu Fandy Artha Gunawan; Arley Sadra Telussa; Kartini Lidia; Hyasinta Arlette Nikita (Universitas Airlangga, 2022)
Introduction: Dry eye is a component of computer vision syndrome (CVS) which is affected by the duration of using a visual display terminal (VDT), such as playing online games. Purpose: To analyze the correlation between the duration spent playing online games and the degree of dry eye complaints and quality of life. Methods: This research is cross-sectional research conducted on students of the General Practitioner Study Program, Faculty of Medicine, Universitas Nusa Cendana, Kupang, Indonesia, who play online games through Zoom meetings and Whatsapp with a total sampling method on 47 respondents. Data was acquired through online game playing duration questionnaire and dry eye related quality of life score (DEQS) questionnaire. The inclusion criteria in this research was an active medical student of the Universitas Nusa Cendana, Kupang, Indonesia, who had a habit of playing online games and had good literacy skills. This research used eta square statistical analysis. Results: From the 47 acquired samples, the most prominent acquired sample was male (70.2%). DEQS score that was acquired was vary. The lowest score 0-10 is was present on 25.53% of samples, score 11-74 was present on 72.34% of samples and the highest score (75) is present on 2.1% of samples. Impaired quality of life score was found on dry eye range (31-75). There was no significant correlation between the duration spent online playing games and the degree of dry eye complaints (p = 0.693). There was significant correlation between degree of dry eye complaint and quality of life (p = 0.000). Conclusions: The duration of spent online playing games has no effect on the degree of dry eye complaints. The degree of dry eye complaints can affect the quality of life.